A case of post-traumatic LASH syndrome responsive to indomethacin and melatonin (a man with a unique triad of indomethacin-responsive trigeminal autonomic cephalalgias). (April 2015) - Rozen, Todd D; Beams, Jennifer L
Objective: The objective of this article is to present the first post-traumatic/secondary case of LASH syndrome and the first melatonin-responsive case of LASH. Methods: We present a case report. Results: A 44-year-old man developed three distinct headache syndromes in progression over a 2.5-year time period after a motor vehicle accident. He initially had paroxysmal hemicrania, which he experienced for 15 months, then transitioned to hemicrania continua for 3.5 months, then LASH syndrome, which he endured until he was treated with indomethacin and became pain free. Then after an inability to taper off indomethacin he was placed on melatonin and achieved a pain-free state. Conclusion: This is the first post-traumatic/secondary case of LASH syndrome, the first male patient to be documented with LASH, and the first LASH case to show complete alleviation with melatonin. This patient's unique case history provides another example of how multiple trigeminal autonomic cephalalgias can occur in a single individual. This may be one of the first cases of three distinct trigeminal autonomic cephalalgias developing after trauma.